Self-medication amongst pregnant women in a tertiary care teaching hospital in India - Rangwala, Pooja P.; Chokshi, Anushka S.; Shah, Radhe K.; Thakkar, Ayush S.; Thakker, Yash G.; Dumra, Gurusharan H.; Trivedi, Yamini N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Self-medication is a popular practice in developing countries where there is no strict regulation of drugs sold in local pharmacies. General public is usually unaware of the adverse effects of drugs used for common illness and continue using them without prescription during pregnancy. This study was carried out to know the extent of self-medication practised by pregnant women and various factors associated with it. Methods: A questionnaire based, cross-sectional study of pregnant women visiting the OB GYN-OPD of a tertiary care teaching hospital was conducted. 303 eligible subjects were questioned and statistical analysis was carried out. Results: Total 16.5% women were found to be self-medicating during pregnancy for common conditions like headache (26%), fever (23%) and common cold (19%). Odds Ratio between the self-medicating and non-self-medicating groups for variables like age (<25 years; ≥25 years), education (illiterate; literate) and gestational age (<20 weeks; ≥20 weeks) are 1.6, 2 and 1.73 respectively. Women with a history of self-medicating before pregnancy were significantly more likely to continue doing so during pregnancy (p value <0.00001). Conclusions: A significant proportion of pregnant women have been found to self-medicate without knowing the adverse effects of the drug used. Thus, spreading awareness against this health-predicament is necessary.